Analysis of Implementation of Entertainment Tax Collection Policy in the Order to Increase Regional Tax Revenue at the DKI Jakarta Regional Revenue Agency - Rahadi Pratomo Singgih; Siffa Fitri Anisa; Mira Permatasari (Yayasan Ilomata, 2022)
This study analyzed the implementation of entertainment tax collection policies to increase local tax revenue at the Regional Revenue Agency of DKI Jakarta. This study uses a qualitative descriptive method with the object of research based on primary data (interviews) and secondary data (field research). This study uses the concept of Edward III's theory, namely communication, resources, disposition, and bureaucratic structure. The results of this study indicate that the entertainment tax policy is not optimal because there are still constraints in the communication aspect, namely the lack of direct socialization with entertainment taxpayers, which causes a lack of understanding of taxpayers about local taxes from the information aspect there are still problems with entertainment providers who have not been registered and registered businesses. entertainment as a tax object, as well as the lack of human resources in implementing policies, can affect entertainment tax revenues.